The burden of Neisseria gonorrhoeae infection, risky sexual behavior, and associated risk factors among sexually transmitted infections in a resource-limited setting area of Addis Ababa City, Ethiopia - Andualem, Tesfaye; Belay, Gurja; Desta, Adey F.; Nigussie, Helen; Mulu, Wondemagegn; Desalegn, Asnake; Taddesse, Gizachew; Mekonen, Yonas; Beyene, Degefu (Frontiers in Reproductive Health, 2025)
IntroductionN. gonorrhoeae is the cause of gonorrhea, which is one of the most common public health problems among sexually transmitted infections. The highest incidence of disease occurs in less developed countries, and gonococcal infections are common among adolescents and young adults. Risky sexual behavior (RSB) is also the main concern. It has many consequences on the health system, which is the most risk factor for the transmission of sexually transmitted diseases, particularly gonorrheal diseases. Little is known about the magnitude of gonococcal infection and risky sexual behavior (RSB) in the reproductive age groups.ObjectivesTo assess the burden of Neisseria gonorrhoeae, Risky Sexual Behavior, and Associated Risk Factors among Sexually Transmitted Infections in a Resource-Limited Area of Addis Ababa City, Ethiopia.MethodsA health institution-based cross-sectional study was conducted from April 2023 to December 2024 in Addis Ababa City. A convenient sampling method was used to collect endocervical and urethral sample swabs from 571 study subjects. Samples were cultured onto Thayer Martin Luther agar, and gram staining and biochemical tests were used to confirm the presence of gonococci. A pre-tested and well-structured questionnaire was used to assess risk factors, and data were analyzed using SPSS version 22. Descriptive and logistic analyses were computed. P-values ≤0.05 were considered statistically significant.ResultsOf the total study subjects, 62.2% were females, and 61.6% were urban residents. Moreover, 183 (32.0%) were in the age of >35 years, followed by 170 (29.8%) in the 30–34 years old. The prevalence of N. gonorrhoeae among STI patients was 17.33%, and risky sexual behavior was 56.9%. The odds of N. gonorrhoeae infection were 1.55 times higher among chat users than the non-chat users [AOR = 1.55, 95% CI: (1.32–1.95)]. Similarly, the odds of risky sexual behavior were 10.95 [AOR = 10.95, 95% CI (5.75–20.84)] times higher among STIs who had a new sexual partner than their counterparts.ConclusionThe prevalence of N. gonorrhoeae and risky sexual behavior among STI patients were high. Gender, watching pornographic films, alcohol consumption, and not participating in religious education have been found to increase the risk of experiencing both N. gonorrheae infections and risky sexual behavior.